Caso clínico 01-2019. Mujer de 24 años con cefalea, pérdida de visión y trombosis en miembro inferior - Vásquez, Sergio; Carrasco, Juan; Huamanchumo, Roberto; Umeres, Hugo (Revista Médica Herediana, 2019)
.